Spatial Analysis of Tornado Warning System Understanding and Relationship with Tornado Occurrence - Chesnea A Skeen (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2017)
Tornadoes present a significant threat to life and property. The National Weather Service watch and warning system warns the public of tornadoes. If these warnings are not heeded by the public, the potential fatalities and destruction of property cannot be minimized. Thus, to prevent further loss of life and property, it is necessary to understand how the public understands the watch and warning system, as well as how they react. This paper aims to understand the correlation between understanding of watches and warnings and the occurrence of tornadoes, as well as how understanding varies spatially. Survey data were collected from 12 Tennessee counties on watch and warning understanding and compared with tornado GIS data from the NOAA Storm Prediction Center tornado database. Survey responses were coded into categories based on response correctness and percentages of “correct” and “incorrect” responses were organized by county, compared and mapped. There is a weak positive correlation between occurrence of tornadoes and poor watch and warning understanding, which p-values prove insignificant. Correlations are stronger when excluding outliers, but remain insignificant. The Memphis area appears to have the poorest watch understanding while the Knoxville area has the best understanding. Warning understanding seems to be the worst in the Knoxville area and best in the Nashville area. Poor watch and warning understanding cannot be predicted by tornado occurrence, so other factors must be affecting understanding. This paper highlights a need for future research and outreach.
Keywords: warning system; tornadoes; watches and warnings; understanding